How We Perceive Others Resembling Us. (November 2020) - Hoffmann, Alexandra; Maran, Thomas; Sachse, Pierre
Eye contact is essential for social cognition, acting as an important tool for social communication. While differences in face scanning patterns concerning familiarity have been thoroughly investigated, the impact of facial similarity on gaze behavior has not been examined yet. We addressed this topic by recording subjects' eye-directed gazing while looking at faces that were individually created systematically varying in terms of similarity to the self-face and familiarity. Subjects' self-faces were morphed into three other faces including a close friend of the same sex. Afterwards, they rated similarity to their self-face of those morphed face stimuli in a separate rating task. Our results show a general preference for the eyes' area as well as differences regarding fixation patterns depending on similarity to the self-face. The lower the similarity to the self-face, the more fixations on the eyes' area. Subjects' ratings followed a linear line, indicating well-pronounced face perception. Nevertheless, other faces were rated faster than the self-face independent of familiarity, while morphed faces got the slowest ratings. Our results mirror the importance of similarity to the self-face as a factor shaping the way we look at the eyes of others explaining variance apart from familiarity.